Labor Market Prospects, Search Intensity and the Transition from College to Work - Aico van Vuuren; Bas van der Klaauw; Peter Berkhout (Institute for the Study of Labor (IZA), 2004)
In this paper we develop a structural model for job search behavior of students entering the labor market. The model includes endogenous search effort and on-the-job search. Since students usually do not start a regular job before graduation but start job search earlier, our model is non stationary even if all structural parameters are constant. The model explains the common finding that a substantial share of individuals starts working immediately upon graduation. We estimate the model using a unique data set of individuals who completed undergraduate education in the Netherlands between 1995 and 2001. Our estimation results show that a 1 percent point decrease in unemployment rate increases wage offers with 3 percent, that there are substantial returns to work experience and that individuals devote less effort to job search than optimal. Employment rates at graduation could be increased from 40 percent to 65 percent if all individuals start job search 6 month prior to graduation.
Keywords: J64; C41; I20; 330; business cycle; structural estimation; return to work experience; Berufseinstieg; Akademische Berufe; Arbeitsuche; Bildungsertrag; Konjunktur; Schätzung; Schätzung; Niederlande; Berufserfahrung